Heart Failure in Cardiac Rehabilitation: A REVIEW AND PRACTICAL CONSIDERATIONS. Issue 5 (14th July 2022) - Keteyian, Steven J.; Michaels, Alexander
Abstract : Few patients with heart failure with reduced ejection fraction enroll in exercise-based cardiac rehabilitation. As such, many miss the benefits garnered from an evidence-based therapy, including an improved exercise capacity, a likely reduction in risk for subsequent clinical events (eg, rehospitalization), improved quality of life, and adoption of disease management strategies. Abstract : Purpose: Exercise cardiac rehabilitation (CR) represents an evidence-based therapy for patients with heart failure with reduced ejection fraction (HFrEF) and this article provides a concise review of the relevant exercise testing and CR literature, including aspects unique to their care. Clinical Considerations: A hallmark feature of HFrEF is exercise intolerance (eg, early-onset fatigue). Drug therapies for HFrEF target neurohormonal pathways to blunt negative remodeling of the cardiac architecture and restore favorable loading conditions. Guideline drug therapy includes β-adrenergic blocking agents; blockade of the renin-angiotensin system; aldosterone antagonism; sodium-glucose cotransport inhibition; and diuretics, as needed. Exercise Testing and Training: Various assessments are used to quantify exercise capacity in patients with HFrEF, including peak oxygen uptake measured during an exercise test and 6-min walk distance. The mechanisms responsible for the exercise intolerance include abnormalities in ( a ) central transport (chronotropic response, stroke volume) and ( b ) the diffusion/utilization of oxygen in skeletal muscles. Cardiac rehabilitation improves exercise capacity, intermediate physiologic measures (eg, endothelial function and sympathetic nervous system activity), health-related quality of life (HRQoL), and likely clinical outcomes. The prescription of exercise in patients with HFrEF is generally similar to that for other patients with cardiovascular disease; however, patients having undergone an advanced surgical therapy do present with features that require attention. Summary: Few patients with HFrEF enroll in CR and as such, many miss the derived benefits, including improved exercise capacity, a likely reduction in risk for subsequent clinical events (eg, rehospitalization), improved HRQoL, and adoption of disease management strategies.